ANÁLISIS TRANSACCIONAL PARA FORMADORES DE MEDIADORES - Mabel López; Cecilia Laruina (European Scientific Journal, ESJ, 2015)
We present a pilot project based on the fact that the Students Trainers of School Mediators handles the techniques of Effective Communication by applying the following instruments of Transactional Analysis: Personality Model (PAC: Parent-Adult - Child ), Behavioral Signs, Transactions, Stroke, Existential Positions, and Emotions. However, it makes the student to be able to understand their own behaviors and to set goals for change of a better school life.